High-damping asphalt material and preparation method thereof

By adding nanoclay, rubber particles, modified fillers and other components to the asphalt materials, the damping performance, temperature resistance and noise reduction effects of traditional asphalt materials are improved, and the shortcomings of traditional asphalt materials in high temperature, low temperature and noise are solved, and the high standard needs of modern transportation construction are met.

CN119592091APending Publication Date: 2025-03-11XUZHOU TRANSPORTATION BUREAU +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895333.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional asphalt materials have shortcomings in high temperature stability, low temperature crack resistance, aging resistance and traffic noise reduction, which is difficult to meet the needs of modern transportation construction and environmental protection.

Method used

High-dampening asphalt materials are used, and their raw materials include matrix asphalt, nanoclay, rubber particles, diatomaceous earth, basalt fibers and modified fillers. The damping performance is improved through the combination of nanoclay and rubber particles. The coupling agent modifies carbon nanotubes and aluminosilicates to improve the dispersion performance of the modified fillers and enhances the material's temperature resistance and noise reduction effect.

Benefits of technology

It improves the damping performance, temperature resistance and noise reduction effect of asphalt materials, and meets the high standard demand for material performance in modern transportation construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201650230000071
    Figure BDA0005201650230000071
  • Figure BDA0005201650230000081
    Figure BDA0005201650230000081
Patent Text Reader

Abstract

The invention relates to the technical field of road construction materials, and particularly discloses a high-damping asphalt material and a preparation method thereof. The high-damping asphalt material is prepared from the following raw material components in parts by weight: 90 to 110 parts of matrix asphalt, 2 to 3 parts of nano clay, 5 to 15 parts of rubber particles, 2 to 5 parts of diatomite, 5 to 10 parts of basalt fiber and 3 to 5 parts of modified filler, the modified filler is prepared from the following raw materials: a coupling agent, carbon nanotubes and aluminosilicate. The preparation method of the high-damping asphalt material comprises the following steps: heating and melting the matrix asphalt, then adding the nano clay, the rubber particles, the diatomite, the basalt fibers, the modified filler and other auxiliaries, and uniformly stirring and mixing to obtain the high-damping asphalt material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of road construction materials, and in particular to a high-damping asphalt material and a preparation method thereof. Background Art

[0002] Although traditional asphalt materials are widely used in road paving, they have obvious deficiencies in high temperature stability, low temperature crack resistance, aging resistance and traffic noise reduction. With the acceleration of urbanization, people's requirements for road comfort and environmental quality are increasing. Traditional asphalt materials can no longer meet the needs of modern transportation construction and environmental protection. The common asphalt mixture currently used is easy to soften and deform at high temperatures, has poor crack resistance under low temperature conditions, and lacks good sound absorption and vibration reduction performance. Especially on busy urban roads, noise pollution has become a major social problem. Summary of the invention

[0003] In order to improve the noise reduction effect of asphalt materials, the present application provides a high-damping asphalt material and a preparation method thereof.

[0004] In the first aspect, the present application provides a high damping asphalt material, which adopts the following technical solution: A high damping asphalt material, the raw materials of the asphalt material include the following components in parts by weight: 90-110 parts of base asphalt, 2-3 parts of nano clay, 5-15 parts of rubber particles, 2-5 parts of diatomaceous earth, 5-10 parts of basalt fiber, and 3-5 parts of modified filler; the raw materials of the modified filler include coupling agent, carbon nanotubes, and aluminosilicate.

[0005] By adopting the above technical scheme, the damping performance of asphalt can be improved by using the combination of nano clay and rubber particles. The coupling agent is used to modify the carbon nanotubes and aluminosilicates to improve the dispersion performance of the modified filler, so that the carbon nanotubes and aluminosilicates are evenly loaded on the basalt fibers. The carbon nanotubes and aluminosilicates not only have a certain noise reduction effect, but also can improve the temperature resistance of the asphalt material. The combination of diatomaceous earth and basalt fibers can further improve the noise reduction effect of the asphalt material.

[0006] In a specific embodiment, the method for preparing the modified filler comprises the following steps: The coupling agent, ethanol and water are stirred and mixed uniformly to obtain a modified solution; The carbon nanotubes and aluminosilicate are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, a modification liquid is sprayed into the mixture. After the spraying is completed, the mixture is continuously stirred and dried to obtain a modified filler.

[0007] By adopting the above technical scheme, the coupling agent is first dissolved in ethanol to obtain a modified liquid, and then the modified liquid is sprayed while the mixture is stirred. After the spraying is completed, stirring is continued, and finally drying is performed to obtain a modified filler.

[0008] In a specific embodiment, the weight ratio of the modified liquid to the mixed material is 1:(13-14).

[0009] By adopting the above technical solution, the ratio of the modified liquid to the mixed material is further limited, thereby improving the modification effect on the carbon nanotubes and aluminosilicate.

[0010] In a specific embodiment, the rubber particles include one or more of nitrile rubber, EPDM rubber, and graphene-modified butyl rubber.

[0011] In a specific embodiment, the rubber particles have a particle size of 50-100 microns.

[0012] By adopting the above technical solution, the particle size of the rubber particles is further limited, so that the rubber particles can be more evenly dispersed in the asphalt material.

[0013] In a specific embodiment, the raw material of the asphalt material further includes 3 to 7 parts by weight of mineral powder and 0.1 to 1 parts by weight of cellulose fiber.

[0014] By adopting the above technical solution, the addition of mineral powder and cellulose fiber can not only improve the stability of asphalt materials, but also improve the temperature resistance of asphalt.

[0015] In a specific embodiment, the mineral powder includes one or more of limestone powder, talc powder, and silicate powder.

[0016] In a specific embodiment, the raw material of the asphalt material further includes 0.1 to 0.5 parts by weight of dioctyl phthalate.

[0017] By adopting the above technical solution, dioctyl phthalate can effectively improve the flexibility and ductility of asphalt materials, and further enhance its performance stability in low temperature environments.

[0018] In a specific embodiment, the raw material of the asphalt material further includes 0.3 to 0.7 parts by weight of butylated hydroxytoluene.

[0019] By adopting the above technical solution, the addition of butylated hydroxytoluene can further improve the stability of the asphalt material.

[0020] In the second aspect, the present application provides a method for preparing a high damping asphalt material, which adopts the following technical solution: A method for preparing a high damping asphalt material comprises the following steps: The base asphalt is heated and melted, and then nano clay, rubber particles, diatomaceous earth, basalt fiber, modified filler and other additives are added, stirred and mixed evenly to obtain a high damping asphalt material.

[0021] By adopting the above technical solution, the base asphalt is first heated and melted, and then nano clay, rubber particles, diatomaceous earth, basalt fiber, modified filler and other additives are added and stirred to obtain a high-damping asphalt material with good noise reduction effect.

[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. In this application, the damping performance of asphalt can be improved by using nano clay and rubber particles. The coupling agent modifies carbon nano tubes and aluminosilicate to improve the dispersion performance of the modified filler, so that the carbon nano tubes and aluminosilicate are evenly loaded on the basalt fiber. The carbon nano tubes and aluminosilicate not only have a certain noise reduction effect, but also can improve the temperature resistance of the asphalt material. The combination of diatomaceous earth and basalt fiber is used again, thereby improving the noise reduction effect of the asphalt material; 2. The addition of mineral powder and cellulose fiber in this application can not only improve the stability of asphalt materials, but also improve the temperature resistance of asphalt; 3. The method of the present application is to first heat and melt the base asphalt, then add nano clay, rubber particles, diatomaceous earth, basalt fiber, modified filler and other additives, stir, and obtain a high damping asphalt material with good noise reduction effect. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments.

[0024] All raw materials in the examples can be obtained from the market. The base asphalt has a CAS number of 8052-42-4; the rubber particles include but are not limited to a mixture of one or more of nitrile rubber, EPDM rubber, and graphene-modified butyl rubber, and nitrile rubber is preferred in this application; the mineral powder includes but is not limited to a mixture of one or more of limestone powder, talcum powder, and silicate powder, and limestone powder is preferred in this application.

[0025] Preparation Example Preparation Example 1 Preparation Example 1 provides a method for preparing a modified filler, comprising the following steps: The coupling agent, ethanol and water are stirred and mixed evenly to obtain a modified liquid; wherein the coupling agent is γ-aminopropyltriethoxysilane, and the weight ratio of the coupling agent, ethanol and water is 5:18:2; The carbon nanotubes and aluminosilicate are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, the modifying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is stirred for 0.5 hours, and then dried at 100°C for 0.5 hours to obtain a modified filler; wherein the weight ratio of the carbon nanotubes to the aluminosilicate in the mixture is 1:1; and the weight ratio of the modifying liquid to the mixture is 1:12.5.

[0026] Preparation Example 2 Preparation Example 2 provides a method for preparing a modified filler, comprising the following steps: The coupling agent, ethanol and water are stirred and mixed evenly to obtain a modified liquid; wherein the coupling agent is γ-aminopropyltriethoxysilane, and the weight ratio of the coupling agent, ethanol and water is 5:18:2; The carbon nanotubes and aluminosilicate are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, the modifying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is stirred for 0.5 hours, and then dried at 100°C for 0.5 hours to obtain a modified filler; wherein the weight ratio of the carbon nanotubes to the aluminosilicate in the mixture is 1:1; and the weight ratio of the modifying liquid to the mixture is 1:13.

[0027] Preparation Example 3 Preparation Example 3 provides a method for preparing a modified filler, comprising the following steps: The coupling agent, ethanol and water are stirred and mixed evenly to obtain a modified liquid; wherein the coupling agent is γ-aminopropyltriethoxysilane, and the weight ratio of the coupling agent, ethanol and water is 5:18:2; The carbon nanotubes and aluminosilicate are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, the modifying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is stirred for 0.5 hours, and then dried at 100°C for 0.5 hours to obtain a modified filler; wherein the weight ratio of the carbon nanotubes to the aluminosilicate in the mixture is 1:1; and the weight ratio of the modifying liquid to the mixture is 1:13.5.

[0028] Preparation Example 4 Preparation Example 4 provides a method for preparing a modified filler, comprising the following steps: The coupling agent, ethanol and water are stirred and mixed evenly to obtain a modified liquid; wherein the coupling agent is γ-aminopropyltriethoxysilane, and the weight ratio of the coupling agent, ethanol and water is 5:18:2; The carbon nanotubes and aluminosilicate are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, the modifying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is stirred for 0.5 hours, and then dried at 100°C for 0.5 hours to obtain a modified filler; wherein the weight ratio of the carbon nanotubes to the aluminosilicate in the mixture is 1:1; and the weight ratio of the modifying liquid to the mixture is 1:14.

[0029] Preparation Example 5 Preparation Example 5 provides a method for preparing a modified filler, comprising the following steps: The coupling agent, ethanol and water are stirred and mixed evenly to obtain a modified liquid; wherein the coupling agent is γ-aminopropyltriethoxysilane, and the weight ratio of the coupling agent, ethanol and water is 5:18:2; The carbon nanotubes and aluminosilicate are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, the modifying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is stirred for 0.5 hours, and then dried at 100°C for 0.5 hours to obtain a modified filler; wherein the weight ratio of the carbon nanotubes to the aluminosilicate in the mixture is 1:1; and the weight ratio of the modifying liquid to the mixture is 1:14.5.

[0030] Preparation Example 6 Preparation Example 6 provides a method for preparing a modified filler, comprising the following steps: The coupling agent, ethanol and water are stirred and mixed evenly to obtain a modified liquid; wherein the coupling agent is γ-aminopropyltriethoxysilane, and the weight ratio of the coupling agent, ethanol and water is 5:18:2; The carbon nanotubes are stirred, and during the stirring process, the modified liquid is slowly sprayed into the carbon nanotubes. After the spraying is completed, stirring is continued for 0.5 hours, and then drying is carried out at 100°C for 0.5 hours to obtain a modified filler; wherein the weight ratio of the modified liquid to the carbon nanotubes is 1:12.5.

[0031] Preparation Example 7 Preparation Example 7 provides a method for preparing a modified filler, comprising the following steps: The coupling agent, ethanol and water are stirred and mixed evenly to obtain a modified liquid; wherein the coupling agent is γ-aminopropyltriethoxysilane, and the weight ratio of the coupling agent, ethanol and water is 5:18:2; The aluminosilicate is stirred, and during the stirring process, the modified liquid is slowly sprayed into the aluminosilicate. After the spraying is completed, stirring is continued for 0.5 hours, and then drying is carried out at 100° C. for 0.5 hours to obtain a modified filler; wherein the weight ratio of the modified liquid to the aluminosilicate is 1:12.5. Example

[0032] Example 1 Example 1 provides a method for preparing a high damping asphalt material, comprising the following steps: 90 kg of base asphalt is heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of modified filler in Preparation Example 1 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0033] Example 2 Embodiment 2 provides a method for preparing a high damping asphalt material, comprising the following steps: 90 kg of base asphalt is heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of modified filler in Preparation Example 2 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0034] Example 3 Example 3 provides a method for preparing a high damping asphalt material, comprising the following steps: 90 kg of base asphalt is heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of modified filler in Preparation Example 3 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0035] Example 4 Example 4 provides a method for preparing a high damping asphalt material, comprising the following steps: 90 kg of base asphalt is heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of modified filler in Preparation Example 4 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0036] Example 5 Example 5 provides a method for preparing a high damping asphalt material, comprising the following steps: 90 kg of base asphalt is heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of modified filler in Preparation Example 5 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0037] Example 6 Example 6 provides a method for preparing a high damping asphalt material, comprising the following steps: 100 kg of base asphalt is heated and melted, and then 2.5 kg of nano clay, 10 kg of rubber particles, 3.5 kg of diatomaceous earth, 7.5 kg of basalt fiber, and 4 kg of modified filler in Preparation Example 3 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0038] Example 7 Example 7 provides a method for preparing a high damping asphalt material, comprising the following steps: 110 kg of base asphalt is heated and melted, and then 3 kg of nano clay, 15 kg of rubber particles, 5 kg of diatomaceous earth, 10 kg of basalt fiber, and 5 kg of modified filler in Preparation Example 3 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0039] Example 8 Example 8 provides a method for preparing a high damping asphalt material, comprising the following steps: 100 kg of base asphalt is heated and melted, and then 2.5 kg of nano clay, 10 kg of rubber particles, 3.5 kg of diatomaceous earth, 7.5 kg of basalt fiber, 4 kg of modified filler in Preparation Example 3, 5 kg of mineral powder, and 0.5 kg of cellulose fiber are added, and stirred to mix evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns; the mineral powder is limestone powder.

[0040] Example 9 Example 9 provides a method for preparing a high damping asphalt material, comprising the following steps: 100 kg of base asphalt is heated and melted, and then 2.5 kg of nano clay, 10 kg of rubber particles, 3.5 kg of diatomaceous earth, 7.5 kg of basalt fiber, 4 kg of modified filler in Preparation Example 3, 5 kg of mineral powder, 0.5 kg of cellulose fiber, and 0.3 kg of dioctyl phthalate are added, and stirred to mix evenly to obtain a high damping asphalt material; the rubber particles are nitrile rubber, and the particle size is 50-100 microns; the mineral powder is limestone powder.

[0041] Example 10 Embodiment 10 provides a method for preparing a high damping asphalt material, comprising the following steps: 100 kg of base asphalt is heated and melted, and then 2.5 kg of nano clay, 10 kg of rubber particles, 3.5 kg of diatomaceous earth, 7.5 kg of basalt fiber, 4 kg of modified filler in Preparation Example 3, 5 kg of mineral powder, 0.5 kg of cellulose fiber, 0.3 kg of dioctyl phthalate, and 0.5 kg of butylated hydroxytoluene are added, and the mixture is stirred and mixed evenly to obtain a high damping asphalt material; the rubber particles are nitrile rubber, and the particle size is 50-100 microns; the mineral powder is limestone powder.

[0042] Comparative Example Comparative Example 1 Comparative Example 1 provides a method for preparing a high damping asphalt material, comprising the following steps: 97 kg of base asphalt was heated and melted, and then 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of the modified filler in Preparation Example 1 were added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles were nitrile rubber, and the particle size was 50-100 microns.

[0043] Comparative Example 2 Comparative Example 2 provides a method for preparing a high damping asphalt material, comprising the following steps: 97 kg of base asphalt was heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, and 3 kg of the modified filler in Preparation Example 1 were added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles were nitrile rubber, and the particle size was 50-100 microns.

[0044] Comparative Example 3 Comparative Example 3 provides a method for preparing a high damping asphalt material, comprising the following steps: 93kg of base asphalt is heated and melted, and then 2kg of nano clay, 5kg of rubber particles, 2kg of diatomaceous earth and 5kg of basalt fiber are added and stirred to mix evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber and have a particle size of 50-100 microns.

[0045] Comparative Example 4 Comparative Example 4 provides a method for preparing a high damping asphalt material, comprising the following steps: 90 kg of base asphalt is heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of modified filler in Preparation Example 6 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0046] Comparative Example 5 Comparative Example 5 provides a method for preparing a high damping asphalt material, comprising the following steps: 90 kg of base asphalt is heated and melted, and then 2 kg of nano clay, 5 kg of rubber particles, 2 kg of diatomaceous earth, 5 kg of basalt fiber, and 3 kg of modified filler in Preparation Example 7 are added, and stirred and mixed evenly to obtain a high damping asphalt material; wherein the rubber particles are nitrile rubber, and the particle size is 50-100 microns.

[0047] Performance testing test Noise reduction performance: The asphalt materials in each embodiment and comparative example are made into a rutting plate with a thickness of 7 cm, and then tested by an indoor tire drop method to obtain the surface noise of different rutting plates. The smaller the noise, the better the noise reduction effect of the asphalt material.

[0048] Heat resistance: According to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the asphalt materials in each embodiment and comparative example were tested to obtain the dynamic stability and splitting tensile strength at -10°C. The higher the dynamic stability, the better the high temperature resistance of the asphalt material; the higher the splitting tensile strength, the better the low temperature resistance of the asphalt material.

[0049] Table 1 Performance test results of asphalt materials In combination with Example 1 and Comparative Examples 1-3, the asphalt material in Example 1 has the best noise reduction effect and the best heat resistance. It can be seen that the asphalt material in the present application, by utilizing the combination of nanoclay and rubber particles, can improve the damping performance of asphalt, and the coupling agent modifies the carbon nanotubes and aluminosilicates to improve the dispersion performance of the modified filler, so that the carbon nanotubes and aluminosilicates are evenly loaded on the basalt fibers. The carbon nanotubes and aluminosilicates have a certain noise reduction effect, and the combination of diatomaceous earth and basalt fibers is further utilized to improve the noise reduction effect of the asphalt material, and the carbon nanotubes and aluminosilicates can also improve the heat resistance of the asphalt material.

[0050] Combined with Examples 1-5, the asphalt materials in Examples 2-4 have better noise reduction effects and better temperature resistance. It can be seen that when preparing modified fillers, the ratio of the modified liquid to the mixed material is preferably 1:(13-14), and the modified filler has a better effect.

[0051] Combining Example 1, Comparative Example 4 and Comparative Example 5, the asphalt material in Example 1 has the best noise reduction effect. It can be seen that when preparing the modified filler, the filler is preferably a mixture of carbon nanotubes and aluminosilicate, and the noise reduction effect of the modified filler is better.

[0052] Combining Example 3, Example 6 and Example 7, the asphalt material in Example 6 has the best noise reduction effect and the best temperature resistance. It can be seen that when preparing the asphalt material, increasing the amount of raw materials used will result in the performance of the asphalt material showing a trend of first increasing and then decreasing.

[0053] Combining Example 6 and Example 8, the asphalt material in Example 8 has better temperature resistance. It can be seen that when preparing the asphalt material, adding mineral powder and cellulose fiber to the raw materials can further improve the temperature resistance of the asphalt material.

[0054] Combining Example 8 and Example 9, the asphalt material in Example 9 has better low temperature resistance. It can be seen that when preparing the asphalt material, adding dioctyl phthalate to the raw materials can further improve the low temperature resistance of the asphalt material.

[0055] Combining Example 9 and Example 10, it can be seen that when preparing the asphalt material, adding butylated hydroxytoluene to the raw material can improve the stability of the asphalt material, but has little effect on the noise reduction effect and temperature resistance of the asphalt material.

[0056] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A high damping asphalt material, characterized in that: The raw materials of the asphalt material include the following components in parts by weight: 90-110 parts of base asphalt, 2-3 parts of nano clay, 5-15 parts of rubber particles, 2-5 parts of diatomaceous earth, 5-10 parts of basalt fiber, and 3-5 parts of modified filler; the raw materials of the modified filler include coupling agent, carbon nanotubes, and aluminosilicate.

2. A high damping asphalt material according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: The coupling agent, ethanol and water are stirred and mixed uniformly to obtain a modified solution; The carbon nanotubes and aluminosilicate are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, a modification liquid is sprayed into the mixture. After the spraying is completed, the mixture is continuously stirred and dried to obtain a modified filler.

3. A high damping asphalt material according to claim 2, characterized in that: The weight ratio of the modified liquid to the mixed material is 1:(13-14).

4. The high damping asphalt material according to claim 1, characterized in that: The rubber particles include one or more of nitrile rubber, EPDM rubber, and graphene-modified butyl rubber.

5. The high damping asphalt material according to claim 2, characterized in that: The particle size of the rubber particles is 50-100 microns.

6. The high damping asphalt material according to claim 1, characterized in that: The raw materials of the asphalt material also include 3 to 7 parts by weight of mineral powder and 0.1 to 1 parts by weight of cellulose fiber.

7. A high damping asphalt material according to claim 6, characterized in that: The mineral powder includes one or more of limestone powder, talcum powder and silicate powder.

8. The high damping asphalt material according to claim 1, characterized in that: The raw material of the asphalt material also includes 0.1-0.5 parts by weight of dioctyl phthalate.

9. The high damping asphalt material according to claim 1, characterized in that: The raw material of the asphalt material also includes 0.3-0.7 parts by weight of butylated hydroxytoluene.

10. A method for preparing a high damping asphalt material as claimed in claims 1 to 9, characterized in that: The following steps are involved: The base asphalt is heated and melted, and then nano clay, rubber particles, diatomaceous earth, basalt fiber, modified filler and other additives are added, stirred and mixed evenly to obtain a high damping asphalt material.